Euglycemic diabetic ketoacidosis associated metabolic encephalopathy caused by dapagliflozin: a rare case report - Lulu Chu; Zhenhua Xi; Runzhi Ma; Weiliang Shi; Guoshen Yu (BMC Neurology)
Abstract Background Sodium–glucose cotransporter-2(SGLT-2) inhibitors are a newer class of antidiabetic drugs with the increased risk of euglycemic diabetic ketoacidosis(EuDKA). Encephalopathy is a rare but life-threatening event of EuDKA. Due to paradoxically normal or slightly elevated serum glucose levels, it’s easy to be mimicked by cerebral infarction, structural brain damage, thus leading to delayed diagnosis and causing seriously irreversible brain injury. Case presentation We report severe EuDKA with metabolic encephalopathy secondary to dapagliflozin in a type 2 diabetes mellitus(T2DM) patient.A 72-year-old female was found unconscious 70 minutes ago.Laboratory evaluation revealed a severe metabolic acidosis with an elevated anion gap, and ketones were elevated in the blood and positive in the urine. The patient was eventually diagnosed with metabolic encephalopathy associated with EuDKA and managed accordingly. Conclusions Metabolic encephalopathy is a rare but life-threatening complication of EuDKA caused by SGLT-2 inhibitors, the imaging features are similar to those of other metabolic encephalopathy such as poisoning and hypoxia. The precise pathogenesis of encephalopathy in EuDKA remains poorly understood, potentially resulting from the toxic consequences of electrolyte disturbances, ketosis, and acidosis.Testing the level of ketones is essential for unconscious patients who are taking SGLT-2 inhibitors.